Alcohol consumption and health in Chinese adults: the China Kadoorie Biobank (CKB) - Im, PK (2020)
Background: Alcohol intake has been associated with poor mental health and increased risks of certain cancers and liver diseases. Evidence is limited from China, where disease rates, drinking patterns, and individuals’ tolerability of alcohol differ importantly from Western populations. Methods: The prospective China Kadoorie Biobank recruited >512,000 adults (41% men) aged 30-79 years from 10 diverse areas during 2004-2008. Detailed information about alcohol consumption, mental health, and other characteristics were recorded by questionnaire, with follow-up through linkage with death and disease registries and electronic hospital records. Logistic regression yielded adjusted odds ratios relating problem drinking patterns to mental health. Cox regression yielded adjusted hazard ratios (HRs) relating usual alcohol consumption to disease risks. Results: At baseline, 33% of men drank alcohol regularly (i.e., at least weekly). Among male regular drinkers, the prevalence of heavy episodic drinking (>60g/session) increased between baseline and the second resurvey (30% vs. 35%; 8 years apart), particularly among younger men born in the 1970s (41% vs. 47%). 24% of male regular drinkers reported problem drinking at baseline, which was positively associated with stressful life events, poor mental health (e.g., depression, anxiety, sleep problems), and increased risks for all-cause mortality, hospitalisation, and injuries. Alcohol intake showed positive dose-response associations with risks of incident cancers of the oesophagus (655 events; HR=1.98 [95%CI: 1.79-2.18] per 280g/week higher usual alcohol intake), mouth and throat (236; 1.74 [1.48-2.05]), liver (573; 1.52 [1.31-1.76]), colon and rectum (575; 1.19 [1.00-1.43]), gallbladder (107; 1.60 [1.16-2.22]), and lung (1017; 1.25 [1.10-1.42]), with similar associations among never- and ever-regular smokers. The associations for oesophageal cancer and lung cancer appeared greater among men with low alcohol tolerability. There were also dose-response relationships between alcohol intake and incident liver cirrhosis (408; 1.87 [1.65-2.12]), alcoholic liver disease (ALD) (211; 2.02 [1.79-2.28]), and non-alcoholic fatty liver disease (208; 1.78 [1.42-2.22]). The risks were greater for oesophageal cancer and ALD among daily drinkers, and for liver cancer, liver cirrhosis, and ALD among men usually drinking without meals, compared with their counterparts. Very few women (~2%) drank alcohol regularly which limited the capacity to assess associations with health. Conclusion: Among Chinese men, alcohol consumption was associated with poor mental health, premature death, cancers at multiple sites, and major chronic liver diseases. Certain drinking patterns may further exacerbate the risks.